Impact of a single bout of resistance exercise on serum Klotho in healthy young men - Takuma Morishima (Wiley, 2021)
Abstract Background It has been shown that Klotho protects vascular endothelial function. Given that a single bout of resistance‐exercise‐induced hypertensive stimulus causes endothelial dysfunction, we postulated that acute resistance exercise would reduce serum Klotho levels. In this respect, the reduction in serum Klotho levels would be associated with the response of flow‐mediated dilation (FMD). Therefore, the purpose of this study was to investigate the impact of acute resistance exercise on the Klotho response in serum. In addition, we examined the relationship between the serum Klotho and FMD responses following acute resistance exercise. Methods Twelve untrained men participated in this study (20.4 ± 0.3 years). Following baseline measurements (blood pressure, blood collection, FMD), subjects performed leg extensions, which consisted of 10 repetitions for five sets at 70% of one‐repetition maximum. After the exercise, measurement of blood pressure, blood collection, and FMD assessment were repeated for 60 min. We analyzed Klotho and endothelin‐1 (ET‐1) concentrations in blood serum. Results As expected, the exercise significantly elevated blood pressure and led to decreased FMD (p < 0.05). However, Klotho concentrations were significantly increased following exercise (p < 0.05). No correlation was observed in Klotho and FMD responses following acute resistance exercise. However, there was a significant positive correlation between Klotho and ET‐1 in response to resistance exercise (p < 0.05). Conclusion In conclusion, the present study reveals that serum Klotho significantly increased following a single bout of resistance exercise. However, the increase in Klotho may not associate with the acute reduction in endothelial function.